Observação sistemática dos procedimentos da equipe de enfermagem na coleta de urina para cultura - M.T.B. Valente Sofia
The objective of this paper is to study the quality of procedures utilized by nursing team in urine collect to culture in hospitals and laboratories of São Paulo City.